2012
DOI: 10.3758/s13421-012-0210-8
|View full text |Cite
|
Sign up to set email alerts
|

Widening the boundaries of the production effect

Abstract: Words that are read aloud are more memorable than words that are read silently. The boundaries of this production effect (MacLeod, Gopie, Hourihan, Neary, & Ozubko, Journal of Experimental Psychology: Learning, Memory, and Cognition, 36, 671-685, 2010) have been found to extend beyond speech. MacLeod and colleagues demonstrated that mouthing also facilitates memory, leading them to speculate that any distinct, item-specific response should result in a production effect. In Experiment 1, we found support for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
125
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(154 citation statements)
references
References 26 publications
13
125
0
Order By: Relevance
“…The main explanation of this effect -the distinctiveness account -suggests that words spoken aloud are better remembered because distinctive information is experienced at encoding and can be ''replayed'' at the moment of recollection (MacLeod et al, 2010;Ozubko, Major, & MacLeod, 2014). The production effect is also present, but to a lesser degree, when words are mouthed instead of read aloud (Forrin, MacLeod, & Ozubko, 2012). But the focus of this work is not the differential effects of sensory feedback at the source of production effects.…”
Section: Unexamined Implications Of Cmt On the Learning Of Verbal Formentioning
confidence: 91%
“…The main explanation of this effect -the distinctiveness account -suggests that words spoken aloud are better remembered because distinctive information is experienced at encoding and can be ''replayed'' at the moment of recollection (MacLeod et al, 2010;Ozubko, Major, & MacLeod, 2014). The production effect is also present, but to a lesser degree, when words are mouthed instead of read aloud (Forrin, MacLeod, & Ozubko, 2012). But the focus of this work is not the differential effects of sensory feedback at the source of production effects.…”
Section: Unexamined Implications Of Cmt On the Learning Of Verbal Formentioning
confidence: 91%
“…Begg & Snider, 1987). In sum, the breadth of materials and encodings that can benefit from a production boost appears to be extensive, a point underscored by Forrin, MacLeod, and Ozubko (2011), who showed reliable enhancements for spelling, typing, and writing, among other modes of production.…”
mentioning
confidence: 99%
“…A series of studies conducted in the field of memory research has shown that words produced aloud are remembered better than words read silently (Forrin, Ozubko & MacLeod, 2012;MacLeod, Gopie, Neary, & Ozubko, 2010;Ozubko, Hourihan, & MacLeod, 2012); this production effect is all the stronger when the production is self-performed (MacLeod, 2011). These findings could have implications for reference reuse in dialogue.…”
mentioning
confidence: 99%